2017
DOI: 10.1093/jpepsy/jsx064
|View full text |Cite
|
Sign up to set email alerts
|

Use of Unannounced Telephone Pill Counts to Measure Medication Adherence Among Adolescents and Young Adults Living With Perinatal HIV Infection

Abstract: Despite challenges, this procedure can be implemented with this population and can help identify adherence barriers important for interventions that address medication-taking behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Longitudinal assessment would provide a clearer picture of patients' adherence over time, including the extent to which the same patients were persistently nonadherent (which could allow them to be targeted for additional support if identified) and what proportion of patients had sufficient cumulative adherence to receive preventive benefits. Finally, because we were not able to review pharmacy logs or patients' prescription bottles, we are unable to assess whether other more easily-observed data, such as refill records or pill counts [30], could have helped in identifying patients with suboptimal adherence. In summary, we observed urine metabolite evidence of >30% recent nonadherence to isoniazid preventive therapy among patients with HIV in two high-burden countries.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal assessment would provide a clearer picture of patients' adherence over time, including the extent to which the same patients were persistently nonadherent (which could allow them to be targeted for additional support if identified) and what proportion of patients had sufficient cumulative adherence to receive preventive benefits. Finally, because we were not able to review pharmacy logs or patients' prescription bottles, we are unable to assess whether other more easily-observed data, such as refill records or pill counts [30], could have helped in identifying patients with suboptimal adherence. In summary, we observed urine metabolite evidence of >30% recent nonadherence to isoniazid preventive therapy among patients with HIV in two high-burden countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to % adherence, a pre‐planned cut‐off of <80% adherence defined “low‐adherence” and ≥80% defined “high‐adherence,” a cut‐off that is commonly used in clinical trials and adherence research, and in a prior TODAY study when participants were youth 16 . Unannounced pill counts have been used extensively in studies of persons with HIV, including young adults 17 . Phone pill counts are reliable and valid compared to scheduled and in‐person home pill counts 18–20 .…”
Section: Methodsmentioning
confidence: 99%
“…16 Unannounced pill counts have been used extensively in studies of persons with HIV, including young adults. 17 Phone pill counts are reliable and valid compared to scheduled and inperson home pill counts. [18][19][20] They have shown significant correlation with HIV viral load, establishing criterion validity.…”
Section: Adherence To Oral Hypoglycemia Agentsmentioning
confidence: 99%
“…Multiple studies have shown that a telephone pill count can be used as a valid alternative for a homevisit pill count. [10][11][12][13][14][15][16] These studies reported high intraclass correlation coefficients (ICCs) ranging between 0.98 and 0.99 when comparing the telephone pill count to a home-visit pill count [10][11][12] and also showed that a telephone pill count is a feasible and practical method. [10][11][12][13][14]16 However, previous studies were primarily conducted in people with HIV, [10][11][12][13]15 who are generally younger than people with T2D and CVD, take less different types of medication, and have fewer comorbidities.…”
Section: Corresponding Authormentioning
confidence: 99%
“…Multiple studies have shown that a telephone pill count can be used as a valid alternative for a home‐visit pill count 10–16 . These studies reported high intraclass correlation coefficients (ICCs) ranging between 0.98 and 0.99 when comparing the telephone pill count to a home‐visit pill count 10–12 and also showed that a telephone pill count is a feasible and practical method 10–14,16 .…”
mentioning
confidence: 99%